Customer Preference and Satisfaction Towards Mobile Network Service Providers in Greater Mumbai Metropolitan Region - John, Jackson; Rane, Adwait (SFIMAR Research Review, 2021)
Telecom is one of the fastest-growing industries in India and the second largest market in the world. With the advanced technologies like 3G, 4G etc. and growing numbers of service operators the competition has increased substantially. Day by day mobile network operators are stepping-up their resources and efforts to improve their services so as to give maximum to their customer. Due to excess competition in the cellular service industry, mobile network operators try to attract new customers and maintain loyalty with the existing customers. The present study deals with customer preference and their satisfaction level towards mobile network service providers, especially during the nationwide lockdown period caused by COVID-19 pandemic. This study highlights the parameters which consumers examine while selecting the particular mobile network operator. It also identifies the consumer satisfaction level for their current operator. This study is especially important given that during lockdown a great majority of the masses have been spending a large chunk of their day working from home or other such activities that require constant use of mobile phone network and mobile hotspot data. The current study was conducted on 119 respondents of Greater Mumbai Metropolitan Region. For collecting the primary data, a structured questionnaire was used. Respondents were selected on Non-Probability convenience sampling basis. This study also tests whether the level of satisfaction affects the continuity with current service provider and there is a likelihood to recommend others. Regression analysis has been used to test the hypotheses.